THE SECOND SCIENTIFIC AND TECHNICAL REVOLUTION AND THE DEVELOPMENT OF GLOBAL PRODUCTION FORCES: https://doi.org/10.5281/zenodo.16759835 - Bozorboyev , Diyorbek (Science technology&Digital finance, 2024)
In this work, the essence of the second scientific and technological revolution, its impact on the development of world production forces and its role in the process of technological renewal of the industry are highlighted. The study analyzed scientific discoveries of the late 19th and early 20th centuries, advances in new energy sources, automation, chemistry, and electrical engineering, revealing their impact on productivity and the international division of Labor.